2022
DOI: 10.1097/mop.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of paediatric type 1 diabetes

Abstract: Purpose of reviewThis article reviews recent developments in methods used to monitor paediatric type 1 diabetes (T1D), including an examination of the role of glycated haemoglobin (haemoglobin A1c) and its limitations for long-term assessment of glycaemia in individual patients, self-monitoring of blood glucose, continuous glucose monitoring (CGM) systems and ketone monitoring. Recent findingsMonitoring of glycemia and ketones, when indicated, is a cornerstone of paediatric T1D management and is essential to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Stable glycemic control can be achieved via a balance between pharmacological approach and nutrition [ 63 , 64 ]. However, despite medical advances, only 20% of children with T1D succeeds in reaching a target of HbA1c <7.5% [ 65 , 66 ]. Much interest has been given to diets characterized by a reduced carbohydrate intake, because it has been observed that lower carbohydrate consumption is associated with a greater glycemic stability [ 67 ].…”
Section: Studies Focusing On Diets Characterized By Different Quantit...mentioning
confidence: 99%
“…Stable glycemic control can be achieved via a balance between pharmacological approach and nutrition [ 63 , 64 ]. However, despite medical advances, only 20% of children with T1D succeeds in reaching a target of HbA1c <7.5% [ 65 , 66 ]. Much interest has been given to diets characterized by a reduced carbohydrate intake, because it has been observed that lower carbohydrate consumption is associated with a greater glycemic stability [ 67 ].…”
Section: Studies Focusing On Diets Characterized By Different Quantit...mentioning
confidence: 99%